Natural products in treating diabetic kidney disease: a visualized bibliometric analysis - Liu, Tianlong; Li, Xiaolin; Chen, Yidan; Li, Jinhu; Wang, Rong; Ding, Yi; Liu, Minna (Frontiers in Pharmacology, 2025)
BackgroundDiabetic kidney disease (DKD) is one of the most significant complications in diabetic patients, yet current therapeutic options are limited. The advantages of natural products in treating chronic diseases have increasingly garnered attention. This study aims to map the landscape of natural products in DKD and provide new insights for future research in this field.MethodsLiterature retrieval was conducted through the Web of Science. CiteSpace and VOSviewer were employed to conduct visual analyses of these papers.ResultsA total of 523 literature were obtained, originating from 655 institutions across 40 countries/regions and involving 3,116 authors. These literature were published in 178 journals. The results indicate that China leads in this field, with Li Ping contributing the most publications. Zhang Lei’s work has been cited the most. Journal of Ethnopharmacology is the most popular journal. The paper with the highest average annual citation rate is authored by Tang, GY. Keyword analysis reveals that systematic biological approaches such as network pharmacology, molecular docking, and gut microbiota have become hotspots in this field.ConclusionNatural products exhibit positive pharmacological activity and therapeutic value in the treatment of DKD. Extensive cooperation and communication among countries, institutions, and authors still need to be strengthened to promote basic research and clinical applications of natural products. Besides, the deep integration of network pharmacology with artificial intelligence and big data represents a hot topic and trend in future research on natural products against DKD.